Proses Pemutakhiran Data Pemilih dalam Melindungi Hak Pilih Pada Pemilihan Walikota dan Wakil Walikota Makassar 2020 - Cenne, Arfandi A; Muhammad; Sukri (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
The problem of this researcher is that the potential voters revealed by Disdukcapil to the Makassar City KPU RI to the Makassar City KPU are 1,048,151 million voters. Voter data updating is needed considering that in this initial voter data there are still many double data and anomalous voter data. the purpose of this research is to explain and analyze the Makassar City KPU Process on updating voter data in protecting people's voting rights in the 2020 election for Mayor and Deputy Mayor of Makassar. The research method used in this research is a qualitative approach. The qualitative approach in this research is an analytical understanding process based on the methodology used. The results of the study There were additional polling stations and a shift in the number of voters from the DPSHP to the DPT, initially the 2020 Election DPSHP of 899,932 voters increased by 1,155 voters, causing the 2020 Election DPT to become 901,087 voters. The conclusion of the results of this study is that the process faced by the Makassar City KPU in the voter data updating stage is the submission of the Election Voters Potential Population List (DP4) updated to the Voters List of Updating Results (DPHP) at the village and sub-district levels and then determined to be the Temporary Voters List (DPS) at the city level. It is updated again to become the Temporary Voters List of Updating Results (DPSHP) at the urban village and sub-district levels and is determined to be the Permanent Voters List (DPT) at the city level.